Optimising radiotherapy of liver tumours: radiobiology of yttrium-90 microsphere treatment - Abbott, EM (2019)
Background: Yttrium-90 selective internal radiotherapy (90Y SIRT) is a treatment aimed at improving tumour control within the liver, from which the disease burden is the most common cause of death. FOXFIRE, SIRFLOX, SARAH and other phase 3 clinical trials of SIRT indicated response in the liver but not increased overall survival. The present work aims to address this phenomenon and hypothesises that optimising treatment around absorbed dose to the liver would result in improved patient outcomes. In addition, the present work hypothesises that treatment planning could be further optimised by considering the factors of radiosensitivity, perfusion, and treatment paradigms to enhance uncomplicated tumour control in the liver and therefore overall survival.